Dispensing Guideline of Dry Powder Inhaler for Asthmatic and Chronic Obstructive Pulmonary Disease Patients at Out-Patient Dispensing Department - Karnchanok Maliphan (Journal of Health Science and Medical Research (JHSMR), 2012)
Asthma and chronic obstructive pulmonary disease (COPD) are chronic airway disorders. The patients must receive suitable management to control progression and prevent disease exacerbation. The main purposes of this study were 1) to design dispensing guideline of dry powder inhaler for asthma and COPD patients who receive dry powder inhaler and 2) to evaluate patients’ technique in using inhaler devices. This study was conducted in the out-patient department. Researchers created dispensing guideline, evaluated following of physicians from 73 patients during October to February 2010 No patients had Inspiratory Peak Flow (IPF) lower than 30 liter/minute. Result are present as descriptive statistics. Measured variables consist of evaluated patients’ suitable IPF and patients’ technique in using inhaler devices. Seventy-three patients (asthma 56, COPD 17) were enrolled IPF ranged from 95-120 l/min in 28 patients (38.35%), 64-94 l/min in 25 patients (34.25%) and 33-63 l/min in 20 patients (27.40%). The results suggested that patients could have IPF>30 l/min through dry powder inhaler. The most common inhaler device that patients made error were Accuhaler, Turbuhaler and Easyhaler, respectively. Fifty-eight patients used inhaler devices correctly at every step before the intervention. In patients who used inhaler devices incorrectly needed to be given repeated a intervention to help them the device correctly.